The Main Character’s Conflicts in Maleficent: An Allegory for Coping Mental Crisis after Pandemic - Lestari, Fira; Sari, Retno Purwani (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
This study aims to describe the psychological aspects of Malificent’s main character as she encounters conflicts. It focuses on how the main character’s maturity grew as a result of the conflicts she encountered, and how she dealt with and coped with the problems. From psychoanalysis perspectives, the character’s struggle may result in personality changes. This qualitative descriptive study made use of Freud’s psychodynamics. Using a closed reading while watching the film, data were taken, collected, and classified to present the relationship between conflicts and character changes. The findings demonstrate that the psychoanalytic concepts of id, ego, and superego are at work in the development of the main character Maleficent's personality changes. The changes represent the character’s maturity. Since the film’s characters, places and events may be inspired by the real-life world, it is an allegory of the world. The conflicts of the main character may be similar to those of other people in real world. The findings of this study may help people deal with their mental crisis’s aftermath of the pandemic covid-19.